Seeds of Insurrection : Domination and Resistance on Western Cuban Plantations, 1808-1848 - Barcia Paz, Manuel, 1972- (Book collections on Project MUSE., 2008)
On a late September day in 1837, shortly after sunset, a group of six slaves marched into the small Cuban village of Güira de Melena, beating African drums and singing loudly. Alarmed, villagers rushed into the streets with machetes, sabers, and spears, ready to take action against the disobedient slaves. Yet this makeshift parade never evolved into the violent rebellion the villagers expected. Though the slaves who lived on Cuban coffee and sugar plantations sometimes defied their captors by orchestrating fierce uprisings and committing murder and suicide, they also resisted in less overt ways.